Is Carcinoma in Columnar-lined Esophagus Always Located Adjacent to Intestinal Metaplasia?: A Histopathologic Assessment. (February 2015) - Aida, Junko; Vieth, Michael; Shepherd, Neil A.; Ell, Christian; May, Andrea; Neuhaus, Horst; Ishizaki, Tatsuro; Nishimura, Makoto; Fujiwara, Mutsunori; Arai, Tomio; Takubo, Kaiyo
Abstract : Diagnostic criteria for Barrett esophagus in the United States and elsewhere, except the United Kingdom and Japan, include the presence of intestinal metaplasia with goblet cells. We analyzed high-grade dysplasia and adenocarcinoma in a complete series of sections of all interfaces between carcinoma in columnar-lined esophagus (CLE) and the adjacent mucosa, assessed them for the mucosal types present, and calculated the proportion of each mucosal type in each case. The materials were a consecutive series of 100 endoscopic resection cases, comprising a total of 1251 microscopic sections. After excluding cases in which intestinal-type or cardiac-type mucosa was not adjacent to CLE carcinoma, 70 cases remained, for which 885 sections were available. Whether the adjacent mucosa was primarily cardiac or intestinal in type was assessed, as were the patterns of immunostaining for HGM, MUC-2, and MUC-6. Twenty-four (34.3%) of the 70 CLE carcinomas were completely surrounded by cardiac-type mucosa, and 10 (14.3%) were completely surrounded by intestinal-type mucosa. In 13 (18.6%), the entire non-neoplastic mucosa of the endoscopic resection specimen comprised the cardiac type alone without any intestinal type, and only 3 (4.3%) comprised the intestinal type only, without any cardiac type. From these findings, we consider it unproven histogenetically that the background mucosa of CLE carcinoma is predominantly of the intestinal type. CLE carcinoma was not demonstrated to have a close relationship with CLE mucosa with intestinal metaplasia.